Safety of a Bioactive Polyphenol Dietary Supplement in Pediatric Subjects with Acute Diarrhoea. (7th September 2015) - Sarker, Shafiqul A.; Sultana, Shamima; Pietroni, Mark; Dover, Arthur
Abstract : The hematological and clinical chemistry profile for children aged 6 months to 5 years with acute diarrhoea was measured in a double blind clinical trial. Subjects were randomized to the study group (N = 44 ) given a bioactive polyphenol dietary supplement in oral rehydration solution (ORS) or to the control group (N = 41 ) given distilled water as a placebo in ORS twice daily for up to 4 days. All subjects received 10 mg zinc daily for the 4 days in the study. Venous blood was collected for complete blood count, electrolytes, liver function, and creatinine upon enrollment (baseline) and at the end of 4 days (end of study); mean values were compared by 95% confidence intervals. Overall, blood factors measured either remained the same over the 4 days or increased or decreased at the same levels between the two groups during the study period. All values were within accepted ranges for paediatric subjects except serum AST (SGOT), where the mean value of the study group approached the upper bound of the range on day 4 but was comparable to the value of the control group. Consumption of this supplement twice daily for 4 days is safe for children and infants.